Prognostic indicators for feline craniofacial trauma: a retrospective study of 114 cases - Kelley, Jennifer L.; Hoyer, Naomi K.; Rao, Sangeeta; Rawlinson, Jennifer E. (Frontiers in Veterinary Science, 2023)
Craniofacial traumatic injuries contribute significantly to the morbidity and mortality of domestic felines. Previous studies focused on feline craniofacial injuries have investigated the origin of injury, injuries sustained, and effectiveness of diagnostic tools. The aim of the study is to identify prognostic indicators for feline craniofacial trauma patients and determine their association with negative and positive outcomes. The Veterinary Committee on Trauma (VetCOT) Trauma Registry and Dentistry and Oral Surgery Case Logs were utilized to identify feline craniofacial trauma cases that were presented to Colorado State University’s Veterinary Teaching Hospital between 2014 and 2020. Prognostic indicators evaluated included: etiology of injury, signalment (age and sex), the Modified Glascow Coma Scale (MGCS), Animal Trauma Triage (ATT) scores, craniofacial examination findings, diagnostic imaging technique, and injuries identified via imaging. Outcomes were determined via patient status upon discharge. Outcomes were grouped into the following categories: survival to discharge at initial presentation to CSU Urgent Care (SDIP), survival to discharge after injury treatment/repair by CSU DOSS or another specialty service (SDTX), euthanized due to grave prognosis at initial presentation (EUGP), euthanized due to financial limitations at initial presentation (EUF), and euthanized due to grave prognosis and financial limitations (EUGP + EUF). The continuous data was described using means and standard deviations. To determine the associations of various groupings of clinical signs and imaging findings with outcome a principal component analysis was performed. Patient sex, trauma etiology, cumulative MGCS and ATT scores on initial presentation and clinical signs on initial presentation were identified as prognostic indicators with intact males, vehicular and animal altercations, lower MGCS cumulative scores, higher ATT scores and the presence of altered mentation identified as negative prognostic indicators. Prognostic indicators for feline craniofacial trauma can be associated with outcomes and help guide clinical decision making.